2006
DOI: 10.1021/jm050801i
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel 2-Amino-5-hydroxyindole Derivatives That Inhibit Human 5-Lipoxygenase

Abstract: Compounds that inhibit 5-lipoxygenase (5-LO), the key enzyme in the biosynthesis of leukotrienes (LTs), possess potential for the treatment of inflammatory and allergic diseases as well as of atherosclerosis and cancer. Here we present the design and the synthesis of a series of novel 2-amino-5-hydroxyindoles that potently inhibit isolated human recombinant 5-LO as well as 5-LO in polymorphonuclear leukocytes, exemplified by ethyl 2-[(3-chlorophenyl)amino]-5-hydroxy-1H-indole-3-carboxylate (3n, IC(50) value co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 30 publications
(53 reference statements)
1
26
0
Order By: Relevance
“…A summary of these reports is listed in Table 2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. A summary of these reports is listed in Table 2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Scheme 5 Allen and Weiss Applications Of The Nenitzescu Indomentioning
confidence: 99%
“…A summary of these reports is listed in Table 2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. A summary of these reports is listed in Table 2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Scheme 5 Allen and Weiss Applications Of The Nenitzescu Indomentioning
confidence: 99%
“…[8,9] The 2-amino-1H-indole-3-carboxylate derivatives are found to be biologically active molecules and important intermediates for construction of medicinal molecules. [10,11] Unfortunately, only a few of examples were reported for their synthe-A C H T U N G T R E N N U N G sis, [11a,12] and the starting materials often are not readily available and difficult to prepare. Volovenko et al attempted a synthesis of 2-amino-6-nitroindoles via the reaction of 2-halo-5-nitroanilines and substituted acetonitriles, [13] the result showed that only 2-fluoro-5-nitroaniline containing a strong electron-withdrawing group (nitro) was effective, however, other 2-haloanilines did not work, so the method could not construct diverse 2-amino-1H-indole derivatives.…”
Section: Full Papersmentioning
confidence: 99%
“…In search of pharmacological agents that suppress the biosynthesis of LTs, different types of small molecular inhibitors of 5-LOX have been developed in the past two decades, such as redox inhibitors, iron-chelator agents and non-redox competitive inhibitors 10 , 11 . To date, despite considerable efforts devoted to the development of efficient and safe drugs that target the 5-LOX pathway, only one 5-LOX inhibitor, Zileuton ( 1 , Scheme 1 ), has been approved for asthma treatment 12 , although it still exhibits several drawbacks, including liver toxicity and unfavorable pharmacokinetic profile with a short half-life 3 .…”
Section: Introductionmentioning
confidence: 99%